2012
DOI: 10.1242/dev.087247
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence for the crucial role of SF1 in steroid-producing cells of the testis, ovary and adrenal gland

Abstract: SUMMARYAdrenal and gonadal steroids are essential for life and reproduction. The orphan nuclear receptor SF1 (NR5A1) has been shown to regulate the expression of enzymes involved in steroid production in vitro. However, the in vivo role of this transcription factor in steroidogenesis has not been elucidated. In this study, we have generated steroidogenic-specific Cre-expressing mice to lineage mark and delete Sf1 in differentiated steroid-producing cells of the testis, the ovary and the adrenal gland. Our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
54
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 41 publications
7
54
0
1
Order By: Relevance
“…The orphan nuclear receptor SF1 is known to activate cytochrome p450 genes [24], and sf1 gene knockout studies have reported that SF1 regulates the expression of steroidogenic genes in steroid-producing cells and that ablation of SF1 leads to a loss in cell morphology and cell identity in the ovary [25]. In addition, Sf1 has also been shown to mediate the release of estradiol from granulosa cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…The orphan nuclear receptor SF1 is known to activate cytochrome p450 genes [24], and sf1 gene knockout studies have reported that SF1 regulates the expression of steroidogenic genes in steroid-producing cells and that ablation of SF1 leads to a loss in cell morphology and cell identity in the ovary [25]. In addition, Sf1 has also been shown to mediate the release of estradiol from granulosa cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Zubair et al Zubair et al, 2008) showed that a fetal adrenocorticalspecific enhancer (FAdE) activates and maintains nuclear receptor subfamily 5, group A, member 1 (Nr5a1, also known as Sf1 or Ad4bp) expression only in the fetal adrenal gland. Nr5a1 encodes steroidogenic factor 1 (Sf1), an essential transcription factor for steroidogenesis, proliferation and differentiation of adrenocortical cells (Bland et al, 2004;Buaas et al, 2012;Fatchiyah et al, 2006;Katoh-Fukui et al, 2005;Lala et al, 1992;Luo et al, 1994;Morohashi et al, 1992;Rice et al, 1991;Sadovsky et al, 1995;Val et al, 2007). The adult cortex emerges between the fetal cortex and capsule, ultimately replacing the regressing fetal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the differentiation of FLCs have been studied extensively, and the involvement of transcription factors [Meeks et al, 2003;Cui et al, 2004;Buaas et al, 2012;van den Driesche et al, 2012;Miyabayashi et al, 2013] and growth factors [Yao et al, 2002;Brennan et al, 2003;Tang et al, 2008] has been determined. Both Leydig cell types display morphological and functional differences in addition to developmental timing; interestingly, this includes the capability for steroid production.…”
mentioning
confidence: 99%